Strategies using sexual reproduction to conserve and restore corals: a case study from the Mexican Caribbean - Banaszak, Anastazia T.; Francisco-Ramos, Vanessa; Mendoza Quiroz, Sandra; Grosso-Becerra, María Victoria (Frontiers in Ecology and Evolution, 2025)
Research in the Mexican Caribbean on the use of assisted propagation to produce coral sexual recruits for outplanting onto local coral reefs has resulted in success as measured by the persistence of the recruits despite intensive heat waves and the production of colonies which are reproducing in the wild. This research is based on four cornerstones: 1) accurate prediction of coral spawning dates and times based on an analysis of almost 20 years of data that helps to make for efficient programming of field work to different sites; 2) the optimization of low-cost methods to assist in the sexual reproduction for five reef-building species through to outplanting and monitoring of the recruits in the wild; 3) the cryopreservation of sperm to form a gene bank of six species of reef-building corals for use in the future when environmental conditions improve and 4) knowledge sharing and capacity building of individuals and organizations around the Caribbean to increase the possibilities of success in using these techniques.